Técnicas de Tolerância a Falhas em uma Plataforma para Prototipagem Rápida Usando Microcontroladores - Kruger, Kleber; Iaione, Fabio (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2019)
This paper describes the implementation of fault tolerance techniques (based on data and processing redundancy) in programming of a rapid prototyping platform using microcontrollers. To evaluate performance of these techniques was used a fault injector software and a weather station system as a case study. Experiments simulated faults in sensor readings and faults in SRAM memory regions of the weather station. Finally, the fault-tolerant system performance is presented in comparison with non-fault-tolerant system, considering incidence of failures, processing time, memory and power consumption.